Formulation and Evaluation of Polyherbal Anti-Tanning Soap - Thakare Mayur Nanaji; Dr. Balke Rasika; Yeola Krushna Sunil; Kadam Baneshwar Sunil; Chavan Kuldip Sunil; Dr. Giri Mahendra (Asian Journal of Pharmaceutical Research and Development, 2026)
Among the three formulations, F3 showed the most Polyherbal soaps are topical formulations prepared using natural plant-based ingredients that offer both cleansing and therapeutic benefits for the skin. The present study focuses on the formulation and evaluation of a polyherbal soap incorporating herbal constituents such as Aloe Vera, Curcuma longa (turmeric), neem (Azadirachta indica), papaya (Carica papaya), and lemon (Citrus lemon). These herbs are well known for their antimicrobial, antioxidant, anti- inflammatory, and skin-nourishing properties. The soap was prepared using a melt-and-pour method, where a soap base was melted and blended with herbal extracts, essential oils, and excipients to obtain a uniform mixture, which was then poured into molds and allowed to solidify.The anti-tanning potential of the formulated soap was evaluated using B16F10 melanoma cells. Melanogenesis was induced by α-MSH stimulation, and the effects of soap extract on cell viability, intracellular melanin content, and cellular tyrosinase activity were assessed. The expression of melanogenesis-related proteins (MITF, TYR, TRP-1, and TRP-2) was also evaluated. Balanced overall performance with good texture, pleasant odour, satisfactory pH, high foam height, and good washability. F2 also exhibited acceptable characteristics but had a slightly higher pH. F1 was more skin-friendly in terms of pH and foam retention; however, its rough texture and poor washability reduced its overall acceptability.